Museum visit as an academic engagement activity: teachers’ perspective - Sahani, Chatterjee; Prakasha, G S (Intelektual Pustaka Media Utama, 2025)
The educational value of museums are immense as they are the storehouse ofartifacts depicting history, culture, and science. Teachers must tap this resource to provide students the experiential learning. Bangalore is one of the metropolitan cities of India, hosting variety of museums where artifacts related to various school subjects such as history, geography, science, art, culture, technology, and music are found. Therefore, the present study aims to find out the teachers' perspective on museum visits as an academic engagement activity and a resource for experiential learning. The study employed a descriptive survey design to understand school teachers' perspectives on museum visits in Bangalore. A convenient sampling method yielded 200 complete responses from school teachers. The study revealed that despite knowing about the field trip to museum as a source of learning, teachers revealed several constraints in organization and implementation of such visits. Having understood teachers’ perspective, study suggests future research may delve into students' learning engagement on a field trip.